2014
DOI: 10.1016/j.molcel.2014.03.043
|View full text |Cite|
|
Sign up to set email alerts
|

A Role for WDR5 in Integrating Threonine 11 Phosphorylation to Lysine 4 Methylation on Histone H3 during Androgen Signaling and in Prostate Cancer

Abstract: SUMMARY Upon androgen stimulation, PKN1-mediated histone H3 threonine 11 phosphorylation (H3T11P) promotes AR target genes activation. However, the underlying mechanism is not completely understood. Here, we show that WDR5, a subunit of the SET1/MLL complex, interacts with H3T11P and this interaction facilitates the recruitment of the MLL1 complex and subsequent H3K4 trimethylation (H3K4me3). Using ChIP-seq, we find that androgen stimulation results in a six-fold increase in the number of H3T11P-marked regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 56 publications
5
95
0
3
Order By: Relevance
“…The epigenetic status of prostate cancer cells is modulated by AR binding and the subsequent recruitment of co-activators or co-repressors [14][15][16][17][18] . Acetylation, methylation, phosphorylation, ubiquitylation and ADP ribosylation of histones critically affect transcriptional regulation by ARs [19][20][21] . The main epigenetic mechanism that controls AR binding to DNA in prostate cancer is histone modification by histone acetyltransferases, histone methyltransferases and protein kinases at AR-binding sites (ARBSs) 20,21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic status of prostate cancer cells is modulated by AR binding and the subsequent recruitment of co-activators or co-repressors [14][15][16][17][18] . Acetylation, methylation, phosphorylation, ubiquitylation and ADP ribosylation of histones critically affect transcriptional regulation by ARs [19][20][21] . The main epigenetic mechanism that controls AR binding to DNA in prostate cancer is histone modification by histone acetyltransferases, histone methyltransferases and protein kinases at AR-binding sites (ARBSs) 20,21 .…”
mentioning
confidence: 99%
“…Acetylation, methylation, phosphorylation, ubiquitylation and ADP ribosylation of histones critically affect transcriptional regulation by ARs [19][20][21] . The main epigenetic mechanism that controls AR binding to DNA in prostate cancer is histone modification by histone acetyltransferases, histone methyltransferases and protein kinases at AR-binding sites (ARBSs) 20,21 . Specific epigenetic codes modulate opening of chromatin to induce or repress the expression of proteinencoding genes and non-coding RNAs 11 .…”
mentioning
confidence: 99%
“…Nevertheless, in addition to the previously identified H3S10 dephosphorylation by PP1 [197] and PP2A [198], more recent studies have identified phosphatases for H4S47ph (PP1 and Wip), H3T3ph/S10ph (mitogen activated protein kinase phosphatase 2), and H3T3ph (Repoman/PP1) [199][200][201][202][203][204][205]. Similarly, while earlier studies have identified several phospho-histone binders, such as specific isoforms of 14-3-3 for H3S10ph/S28ph and MDC1 for H2A.XS129ph, more recent studies have identified survivin (H3T3ph), WDR5 (H3T11ph), and shughosin (H2AS120ph) as phospho-histone readers [173,[206][207][208].…”
Section: Histone Phosphorylationmentioning
confidence: 93%
“…After androgen stimulation, protein kinase C-related kinase 1 (PRK1) promotes histone H3 threonine 11 phosphorylation (H3T11P) [19]. WD repeat containing protein 5 (WDR5), a subunit of the SET1/MLL complex, associates with H3T11P and then promotes the recruitment of the MLL complex for H3K4 tri-methylation (H3K4me3) in ARBSs [20]. PRK1 kinase activity facilitates demethylation of H3K9 by cooperating with lysine-specific demethylase 1 (LSD1) [19,21].…”
Section: The Androgen Receptor (Ar) Functions As a Nuclear Receptor Tmentioning
confidence: 99%
“…MLL complex interacts with AR through menin and promotes histone H3K4 methylation to enhance AR dependent gene expression. SRC family or ARA70 are AR interacting cofactors for histone acetylation [18][19][20][21][22][23]. (B) Androgen-induced miRNA mediated TET2 repression inhibits 5-hmC modifications in FOXA1 occupied enhancer regions.…”
Section: The Androgen Receptor (Ar) Functions As a Nuclear Receptor Tmentioning
confidence: 99%